PENGARUH KARAKTER EKSEKUTIF, KUALITAS AUDIT, DAN MANAJEMEN LABA TERHADAP TAX AVOIDANCE - Rifqa Aulia Nabyla (2021)
This study aims to determine the effect of executive character, audit quality, and earnings management on tax avoidance in manufacturing companies listed on the Indonesia Stock Exchange in the 2018-2020 period. This research is a type of quantitative research that uses secondary data in the form of financial statements or company annual reports. The sample in this study were 124 manufacturing companies. The data analysis technique in this study used a regression model selection test, classical assumption test, panel data regression, and partial hypothesis testing (t test). Based on the results of data analysis, it can be concluded that (1) executive character has a significant positive effect on tax avoidance, (2) audit quality has no significant effect on tax avoidance, (3) earnings management has a significant negative effect on tax avoidance, and the control variables are (4) leverage has no significant effect on tax avoidance, and (5) firm size has no significant effect on tax avoidance. Keywords: Executive Character, Audit Quality, Earnings Management, Leverage, Company Size, and Tax Avoidance